EFFECTS OF FOOD ABUNDANCE AND HABITAT STRUCTURE ON SEED-EATING RODENTS IN SPAIN WINTERING IN MAN-MADE HABITATS - Díaz, M.; González, E.; MUNOZPULIDO, R.; NAVESO, M. A. (ZEITSCHRIFT FUR SAUGETIERKUNDE-INTERNATIONAL JOURNAL OF MAMMALIAN BIOLOGY, 1993)
The patterns of abundance and seed (acorn) predation races were analyzed in granivorous rodents (mainly the wood mouse Apodemus sylvaticus L.) wintering in two man-made habitats: cereal croplands, and a kind of wood-pasture exclusive to the western Mediterranean basin, the dehesas. Both seed (acorn) abundance ana vegetation structure were also measured. Within dehesas, neither rodent abundance nor acorn predation rates were related to acorn abundance, whereas there Tvas a significant. association between rodent abundance and shrub cover at the end of winter. These results were coincident with previous findings in croplands. Both rodent abundances and seed predation rates were lower in dehesas than in croplands, despite the better structural and trophic conditions of the first habitat for rodents (larger shrub cover and food abundance). However, the body condition of animals was better in dehesas, to the extent that we found strong evidence for mincer reproduction. Rodent predator communities appear to be more diverse and denser in dehesas than in croplands. This suggests a heavier predation pressure in dehesas which would have culled rodent populations in such a way chat food Tvas plentiful for survivors, rhus explaining their scarcity, good body condition, and low dependence on food resources.
APSAPSThe following values have no corresponding Zotero field: pub-location: VILLENGANG 2, D-07745 JENA, GERMANY publisher: GUSTAV FISCHER VERLAG
Keywords: abundance patterns; acorn predation; Mediterranean; montado; rodents